Treatment with (R)-α-methylhistamine or IL4 stimulates mucin production and decreases Helicobacter pylori density in the murine stomach - Licínia Santos; Sinan Sharba; John Benktander; Stefany Ojaimi Loibman; Macarena P. Quintana-Hayashi; Mattias Erhardsson; Sara K. Lindén (Virulence)
Helicobacter pylori is the most common gastric pathogen. H. pylori is prone to develop antibiotic resistance and recurrence after therapy makes treatment problematic. H. pylori can be detected attached to the gastric epithelial cells; however, it is mostly found within the gastric mucus. Helicobacter species infections impair the mucus barrier by decreasing the binding ability of the mucins, decreasing the growth-limiting activity of mucins and decreasing mucin production. The current study aimed to restore mucin production in the male C57BL/6 mouse H. pylori (SS1) infection model and evaluate its effects on H. pylori density. Mice infected with SS1 were treated with (R)-α-methylhistamine (RαMH) or interleukin-4 (IL4). Treatment with RαMH or IL4 restored mucin production and decreased gastric H. pylori density compared to mock-treated infected mice. Treatment with RαMH and IL4 did not affect serum anti-H. pylori IgG levels, expression of antimicrobial peptides or H. pylori virulence factors. Further, RαMH did not have cytotoxic effects on H. pylori. However, the expression of cytokines (Tnf and Il4), factors related to mucus production (Tff1, Spedf, Stat6, and Ptgs1), and mucin O-glycan sialylation levels differed between mice treated with RαMH and IL4. This suggests that increased mucus production can have similar effects on pathogen density in spite of differences in the local niche. In conclusion, agents that stimulate mucin production in the gastric mucosa have the potential to aid in the removal of pathogens from the gastric niche.